Penerapan Arsitektur Multisensori sebagai Stimulus Multiple Intelligence Anak pada Taman Prestasi Surabaya - Nabila, Faizah Ayu; Maharani, Rizka Tiara (Universitas Medan Area, 2025)
The sensory system is an effort created to increase intelligence for children, one of which is through rides. Visitors to Taman Prestasi are predominantly aged 24-120 months, guided by parents. Taman Prestasi as a children's companion facility should be able to reveal how multisensory principles are applied to hone intelligence not only with theory, but great intelligence in the real world. The research aims to describe the extent of multisensory principles in the park design, by analyzing aspects of children's multiple intelligence consisting of visual-spatial, linguistic, gestural, mathematical logic, musical, intrapersonal, interpersonal, and naturalist intelligence. It is expected that Taman Prestasi can support the stimulation of children to achieve multiple intelligence. The research used descriptive method of qualitative approach by comparing journal samples and combining observations by means of interviews and observations of a sample of 10 children aged 12-72 months divided into 2 age ranges. The results of the study explained that in terms of macro, Taman Prestasi rides meet the criteria of multisensory architecture, but in micro the rides only apply some multisensory theories so that the stimulation of multiple intelligence is less realized.